2018
DOI: 10.22373/jid.v18i2.3240
|View full text |Cite
|
Sign up to set email alerts
|

Learning Strategy: Identifying Strategy Used by Language Learners (For Toefl, Ielts, and Global English Learners)

Abstract: English proficiency test is the most widely taken for many purposes. Most of people take TOEFL, IELTS, and global English as learning fields to achieve their learning purposes. However the score for these proficiency tests are low. Consequently, they need to find solution to increase the score, for instance using learning strategies. There are several language strategies can be used to help them to achieve it. This study focuses on identifying which strategies used by language learners for learning IELTS, TOEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Some can be regarded as good language learners and vice versa. Studies in language learning strategies have shown that good language learners often have strategies in hand and use these strategies in their learning process more often than weak learners (Wang, 2014;Mahalingam, 2016;Mahalingam & Melor, 2016;Munzaki, 2018). They are generally autonomous learners and are more likely to be more successful than those who depend on the teachers (Hedge, 2000).…”
Section: Conceptual Understanding Of Language Learning Strategiesmentioning
confidence: 99%
“…Some can be regarded as good language learners and vice versa. Studies in language learning strategies have shown that good language learners often have strategies in hand and use these strategies in their learning process more often than weak learners (Wang, 2014;Mahalingam, 2016;Mahalingam & Melor, 2016;Munzaki, 2018). They are generally autonomous learners and are more likely to be more successful than those who depend on the teachers (Hedge, 2000).…”
Section: Conceptual Understanding Of Language Learning Strategiesmentioning
confidence: 99%
“…Students are required to engage in numbers of oral practices that they may not have experienced before, these include individual oral presentation, group presentation, video presentation, etc. [7]. Meanwhile, the college itself has also played a role in facilitating its students' passion in learning oral English, such as the weekly English corner, the English cultural festival, and oral English competitions, etc.…”
Section: 2mentioning
confidence: 99%
“…Quotation is a useful tool applied in oral delivery, especially in a public speech [7]. Many speakers would use quotation in the introduction part of a speech to build connection with the famous figure or prominent idea, and it also serves as a practical way to attract audiences' attention.…”
Section: Students' Quotation Ability Has Improved Significantlymentioning
confidence: 99%
“…The study findings supported the hypothesis that more successful students employed LLSs more frequently than less successful students did. In addition, the researchers investigated the strategies used for four language skills (reading, writing, speaking, and listening) and suggested that those who scored 6.0 or more reported using strategies related to all four skills more frequently Strategies used by language learners to achieve high scores in TOEFL and IELTS have been discussed by Munzaki (2018). The results showed that IELTS learners mostly used compensation strategy and social strategy, and the problem found was about learners' inconsistency and instability in using the strategies.…”
Section: Literature Reviewmentioning
confidence: 99%